Mechanical and Metallurgical Characterization of Dissimilar Weld Joints Using Continuous Direct Drive Friction Welding - RENGARAJAN, Sathish; RAO, Vaddi Seshagiri (Engineering Transactions, 2016)
This paper presents studies on continuous direct drive friction welded joints made of low and medium carbon steels. The fractured specimen was examined using a scanning electron microscope and it consisted of fine dimples which showed the mode of ductile fracture. Plasticity which is indicative of the flow of grains was better observed in the low carbon steel side than in the medium carbon steel side. Light microscopy revealed the flow of fine grained austenite partially transformed into a marten-site structure which exhibits more tensile strength. X-ray diffraction test confirmed that the chromium in the weldments is consistently spread and improves corrosion resistance properties.